Recurrent hemoptysis: An unusual cause and novel management - Surya, Praharsha; Keshava, Shyamkumar N; Irodi, Aparna; Vyas, Sunil; Thangakunam, Balamugesh (Indian Journal of Radiology and Imaging, 2016)
We report a rare case a 15 year old boy who presented with recurrent hemoptysis. There was past history of pancreatitis. A CT scan of thorax revealed a small collection in the region of the tail of the pancreas and a tract from it extending across the diaphragm into the posterobasal segment of left lower lobe, suggesting a pancreatico-pleuro-pulmonary fistula. The fistula was embolised by percutaneous injection of glue into the collection and fistula, which resulted in good symptom control.
Keywords: Glue embolization; hemoptysis; pancreatico-pulmonary fistula; pancreatitis